2014
DOI: 10.1021/bi5001728
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted Human Myosin Light Chain Phosphatase Reveals Distinct Roles of Two Inhibitory Phosphorylation Sites of the Regulatory Subunit, MYPT1

Abstract: The myosin light chain phosphatase (MLCP) is a cytoskeleton-associated protein phosphatase-1 (PP1) holoenzyme and a RhoA/ROCK effector, regulating cytoskeletal reorganization. ROCK-induced phosphorylation of the MLCP regulatory subunit (MYPT1) at two sites, Thr696 and Thr853, suppresses the activity, although little is known about the difference in the role. Here, we developed a new method for the preparation of the recombinant human MLCP complex and determined the molecular and cellular basis of inhibitory ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 51 publications
8
74
0
Order By: Relevance
“…21 Currently, phosphorylation of T696 is thought to directly inhibit MLCP activity towards MLC, via pseudosubstrate inhibition, whereas T853 phosphorylation is believed to cause dissociation of MLCP from myosin and/or inhibit MLCP activity directly. 68 The latter hypothesis is supported by the recent study using a genetic approach to knock-in nonphosphorylatable Ala for T852 or T694. 69 The MYPT1 T694A mutation was found to significantly inhibit sustained force as well as MLC phosphorylation, while the T852A mutation had no significant effect on maximal force development and little effect on force maintenance in neonatal bladder smooth muscle.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 85%
“…21 Currently, phosphorylation of T696 is thought to directly inhibit MLCP activity towards MLC, via pseudosubstrate inhibition, whereas T853 phosphorylation is believed to cause dissociation of MLCP from myosin and/or inhibit MLCP activity directly. 68 The latter hypothesis is supported by the recent study using a genetic approach to knock-in nonphosphorylatable Ala for T852 or T694. 69 The MYPT1 T694A mutation was found to significantly inhibit sustained force as well as MLC phosphorylation, while the T852A mutation had no significant effect on maximal force development and little effect on force maintenance in neonatal bladder smooth muscle.…”
Section: Inhibition Of Myosin Light Chain Phosphatase Activity By Mypmentioning
confidence: 85%
“…In terms of bladder smooth muscle, Mizuno et al [24] reported that carbachol stimulation increased MYPT1 Thr696 phosphorylation in mice, being consistent with our current observations. More recently, a report from Khasnis et al [8] demonstrated that selective phosphorylation of MYPT1 at Thr696 with ROCK inhibited the MLCP activity 30%, whereas the Thr853 phosphorylation did not alter the phosphatase activity. Their results suggested that phosphorylation of Thr696 was more stable compared with that of Thr853, and it may facilitate Thr853 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…MLCP is a heterotrimer that consists of three subunits: a 110-kDa regulatory myosin phosphatase-targeting subunit (MYPT1), a 38-kDa catalytic subunit of type 1 phosphatase (PP1c), and a 20-KDa subunit (M20) with unknown function [7]. Lines of evidence suggest that the regulatory MYPT1 subunit play the central role in the inhibition of cellular MLCP, which is essential for smooth muscle contraction [6,8]. Moreover, the inhibition of MLCP activity by Rho-associated protein kinase (ROCK) mediated MYPT1 phosphorylation is thought to act a key role in Ca2+-sensitized contractions of different smooth muscles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer drugs are known to induce apoptosis by activating 47 proapoptotic regulators and at the same time suppressing survival 48 factors [1]. Several signaling pathways may influence the efficacy of the activation of some MAP-kinase types might contribute to the 60 destructive cellular effects.…”
mentioning
confidence: 99%